Mothers/caregivers healthcare seeking behavior towards childhood illness in selected health centers in Addis Ababa, Ethiopia: a facility-based cross-sectional study - Nebiat Teshager Abegaz; Hailemariam Berhe; Gebremedhin Beedemariam Gebretekle (BMC, 2019)
Abstract Background Seeking healthcare in children is unique since parents decide upon the type and frequency of healthcare services accessed. Mothers/caregivers lower healthcare seeking behavior is one of the major reason for increased morbidity and mortality from childhood illness in developing countries. Hence, this study aimed to assess healthcare seeking behavior of mothers/caregivers towards childhood illnesses in selected health centers of Addis Ababa, Ethiopia. Methods A facility-based cross-sectional survey was conducted on 422 sampled mothers/caregivers of children age 0-59 months, from April 18 to May 11, 2016. Ten health centers were selected using simple random sampling technique and proportionate number of participants were included from each health centers. A pre-tested, semi-structured questionnaire was used to collect data. Data were analyzed using SPSS version 20.0. Descriptive statistics was used to summarize socio-demographic characteristics and multivariable logistic regression was employed to identify factors associated with of healthcare seeking behavior. Result In case of illnesses, 26.5% of mothers/caregivers sought healthcare for their children. Among the common childhood illnesses, acute respiratory tract infection and diarrhea accounted for 47.6 and 31%, respectively. Mothers/caregivers healthcare seeking behavior towards common childhood illnesses were influenced by child's age (AOR = 1.78, 95% CI:1.02, 3.13), education of mothers/caregivers (AOR = 4.24, 95% CI:1.32, 13.63), family size (AOR = 3.83, 95% CI:1.06, 13.78), perception of severity of illnesses (AOR = 2.00, 95% CI:1.05, 3.84), previous experience of similar illnesses (AOR = 3.67, 95% CI:1.36, 9.86) and previous history of under-five child death (AOR = 13.31, 95% CI:5.13, 34.53). Conclusions The common under-five childhood illnesses were acute respiratory tract infection and diarrhea. The study also revealed that there was a delay in seeking healthcare and this was significantly associated with age of the child; mothers/caregivers level of education; family size; perception of illness severity; previous experience of similar illnesses and under-five child death.